"The Truth Had Been Twisted and Contorted": Toward a Pragmatics of F. M. Dostoevsky's The Landlady. (1st October 2020) - Kravchuk, Igor
ABSTRACT: This article examines the poetics of Dostoevsky's novella The Landlady (1847) from a pragmatic perspective, approaching it as a literary utterance that manifests a new depictive technique and defends the autonomy of the professional writer within the emerging Russian literary industry. The story's eventive incoherence, which critics and scholars have seen as a failed literary experiment, is the story's organizing principle. The perspicacity of an artist capable of penetrating the protagonists' psychology while avoiding aesthetic convention sets the work apart from both Hoffmanesque fantasy and the factographic precision of the natural school. Dostoevsky's experiment centers on the figure of the main protagonist, a dilletante scholar who combines features of the university intellectual and the unfettered artist. Ordynov's drama echoes Dostoevsky's own—his need to choose between an independent aesthetic position and a place in his era's literary hierarchy.